Waste paper as a music source: fragments preserved with the incunabula at the University Library in Wrocław - Gancarczyk, Paweł (Katedra Muzykologii, Wydawnictwo Naukowe PTPN, Wydawnictwo Naukowe UAM, 2012)
Preserved with the incunabula at the University Library in Wrocław are eighty-fi ve fragments of music manuscripts. Alongside numerous antiphonaries, notated breviaries and missals, they also include a fragment with polyphonic music (PL-WRu XV Q 1066). This contains three compositions typical of fi fteenth-century Central European repertory. There are grounds for supposing that this fragment was written in Silesia during the second quarter of that century. Research into the music fragments from the University Library in Wrocław has provided the author with a point of departure for discussing methodological issues. Questions are raised regarding the nature of fragmentary sources, with reference to the classifi cation of historical sources proposed by Jerzy Topolski. The status of fragments differs from that of sources preserved intact, and this should be refl ected in research procedures, such as the method of establishing provenance. The adoption of new methodological principles requires a critical re-examination of the interpretation of some musical fragments, including the sources preserved in Poland.
Keywords: University Library in Wrocław; music manuscripts; fragmentary sources; chant music; fi fteenth-century polyphony